Overexpression of the Golden SNP-Carrying Orange Gene Enhances Carotenoid Accumulation and Heat Stress Tolerance in Sweetpotato Plants - So-Eun Kim; Chan-Ju Lee; Sul-U Park; Ye-Hoon Lim; Woo Sung Park; Hye-Jin Kim; Mi-Jeong Ahn; Sang-Soo Kwak; Ho Soo Kim (MDPI AG, 2021)
Carotenoids function as photosynthetic accessory pigments, antioxidants, and vitamin A precursors. We recently showed that transgenic sweetpotato calli overexpressing the mutant sweetpotato (Ipomoea batatas [L.] Lam) Orange gene (IbOr-R96H), which carries a single nucleotide polymorphism responsible for Arg to His substitution at amino acid position 96, exhibited dramatically higher carotenoid content and abiotic stress tolerance than calli overexpressing the wild-type IbOr gene (IbOr-WT). In this study, we generated transgenic sweetpotato plants overexpressing IbOr-R96H under the control of the cauliflower mosaic virus (CaMV) 35S promoter via Agrobacterium-mediated transformation. The total carotenoid contents of IbOr-R96H storage roots (light-orange flesh) and IbOr-WT storage roots (light-yellow flesh) were 5.4-19.6 and 3.2-fold higher, respectively, than those of non-transgenic (NT) storage roots (white flesh). The β-carotene content of IbOr-R96H storage roots was up to 186.2-fold higher than that of NT storage roots. In addition, IbOr-R96H plants showed greater tolerance to heat stress (47 °C) than NT and IbOr-WT plants, possibly because of higher DPPH radical scavenging activity and ABA contents. These results indicate that IbOr-R96H is a promising strategy for developing new sweetpotato cultivars with improved carotenoid contents and heat stress tolerance.